Problem Analysis of Asaoka Method on the Post-construction Settlement Prediction of Soft Ground - ZHOU Yuelei; LIU Zhonghan (Renmin Zhujiang)
In view of uncertainty of Asaoka method on the post-construction settlement prediction of soft ground,this paper transforms the measured data at constant time interval through BP neural network with good nonlinear fitting ability,establishes the regression analysis model at different starting points and different time intervals based on Asaoka method,predicts the post-construction settlement by the model and analyze the stability of the predicted value through mathematical methods,as well as comprehensively analyzes the stability of the prediction results with the measured data of a soft foundation treatment project.The analysis results show that:①BP neural network with good nonlinear fitting ability is effectively used in the transformation of the measured data of soft ground;②It is not advisable to judge the reliability of Asaoka method by the correlation coefficient;③The small error of β1 can cause significant error to the prediction results;④The reliability of prediction results can be increased by expanding time interval.